2018
DOI: 10.5539/ijef.v10n12p37
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Financial Development and Economic Growth: Empirical Evidence in Indonesia

Abstract: The aim of this paper to examine the relationship between financial development and economic growth in Indonesia by using data from 1986 until 2014. Johansen co-integration and Granger causality are utilized to analyze the data. The financial development is measured by the ratio of broad money and other control variables such as trade openness and government expenditure. The finding indicates that there is long run relationship between financial development and economic growth. Meanwhile, a unidirectional rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Ariuna and Gibson (2016), using data for China covering the period 1978-2011 and applying the VAR model, concluded that there is a long term relationship between economic growth and financial development. These results are also supported by Akinboade and Kinfack (2015) who used the ARDL for South Africa and also the studies by Magaji, Darma and Igwe (2021) and Hasan (2018), using the Toda-Yamamoto approach to Granger causality.…”
Section: Stock Marketsupporting
confidence: 73%
“…Ariuna and Gibson (2016), using data for China covering the period 1978-2011 and applying the VAR model, concluded that there is a long term relationship between economic growth and financial development. These results are also supported by Akinboade and Kinfack (2015) who used the ARDL for South Africa and also the studies by Magaji, Darma and Igwe (2021) and Hasan (2018), using the Toda-Yamamoto approach to Granger causality.…”
Section: Stock Marketsupporting
confidence: 73%
“…By employing data from Malaysia, Ismail et al (2019) concluded that economic growth precedes the advancement of the financial system. Additionally, Hasan (2018) and Pinshi (2020) reached a similar conclusion for the Indonesian and Congolese economies, and the demand-following hypothesis was generally dominant.…”
Section: Literature Reviewmentioning
confidence: 76%
“…When it comes to the fostering of the financial units, the relationship between prosperity in the financial aspects and fostering of the GDP is also considered to be highly significant that primarily depends on the effectiveness and growth of the financial sectors operating in the country. According to the study conducted by Hasan (2018), in Indonesia, financial institutions and the openness of the country towards international trading play a significant role in boosting the economy towards growth. However, there are various studies that argue on the higher effect of fostering of financial strength on the GDP increase of Indonesia as some studies consider it to be the primary factor and some studies consider it to be a secondary factor for making an economy grow rapidly.…”
Section: Introductionmentioning
confidence: 99%